Efektivitas Ekstrak Daun Pepaya (Carica Papaya) Terhadap Kematian Lalat Rumah (Musca Domestica) - Nur Aini Bunyani; Maya F. Roman; Charizal M.A. Manu (Lembaga Pengembangan Kinerja Dosen, 2022)
This research was carried out at the Laboratory of the Mathematics and Natural Sciences Faculty of the 1945 NTT Teachers' Association University from July to September 2022. With the aim of 1) to determine the effect of papaya leaf extract (Carica papaya) on the death of house flies (Musca domestica). 2) to determine the effectiveness of papaya leaf extract (Carica papaya) against the death of house flies (Musca domestica). The design used in this research was an experimental method for each papaya leaf extract concentration of 1%, 2% and 3% carried out 3 times. . The aim of the experiment was to provide accurate data on the death of house flies (Musca domestica) where the death of house flies that occurred in the study was due to the administration of papaya leaf extract. The results of the research showed that papaya leaf extract could kill house flies. This proves that papaya leaf extract is effective against the death of house flies. The appropriate concentration of papaya leaf extract for the death of houseflies from the tests that have been carried out is at a concentration of 1%, the lowest range and the highest range is 3%.